The Costs of Customer Service Citizenship Behaviors: A Qualitative Study - Lavee, Einat; Pindek, Shani (Frontiers in Psychology, 2020)
Organizational citizenship behaviors (OCBs) – behaviors not formally required or rewarded by the organization, but which promote its effectiveness – can be directed at coworkers, the organization itself or other stakeholders. OCBs directed at customers (customer-oriented citizenship behavior or OCBC) have received surprisingly little attention. Preliminary studies examined the unique contribution that OCBCs make in terms of perceived service quality and customer loyalty. In the current study, OCBCs were conceptualized in terms of supplying informal resources, which are– resources provided outside the worker’s formal role or the organization’s formal goals, or formal resources offered in informal ways (after hours, off duty). Applying a qualitative design, we uncovered types of informal resources and their associated costs. We also examined differences in informal resource provision and costs between occupational groups. Participants were 214 Israeli professionals who offer customer service in the education, health and welfare domains. All participants reported investing informal resources in their customers. Data demonstrated a remarkable range of types of informal resources, including emotional, instrumental and material resources. The most prevalent associated costs were interference with workers’ family life, followed by such personal costs as loss of free time, physical and emotional exhaustion, and material expenditures. Professional costs, which were rarely reported, included time taken from other customers and reduced in-role performance. No differences were detected in the pattern of informal resources between occupational groups: all employees reported high informal investment aimed at increasing customers’ well-being. Some of the implications discussed include the potential organizational costs associated with OCBCs. While such behaviors can improve service quality ratings, they can also lead to depleted employee resources and higher strain, negatively impacting productivity in the long term.